Polish news portals in the view of the documentary entitled Franciszkańska 3: content analysis of the image of John Paul II - Węglińska, Agnieszka; Harbanowicz, Justyna (Kultura Media Teologia, 2024)
The research problem is the image of Karol Wojtyla, who presented five major horizontal por tals in reaction to the documentary Franciszkańska 3. The analysis comprises the first eight days after its broadcast on TVN24. The adopted research perspective is the phenomenon of personalization. The paper aims to analyze how the five most opinion-forming, free news portals presented the person of Karol Wojtyła. The authors in the conducted research, both quantitative and qualitative, verify the hypothesis that in the film and the analyzed texts, in the reactions to the crime of pedophilia among the clergy in the diocese of Krakow are interpreted in the context of Karol Wojtyła’s personal responsibility, not the institution. The research results confirm the above hypothesis.